CARGO INSURANCE AS A KIND OF PROPERTY INSURANCE - Shylo, L. A. (Science and Transport Progress, 2006)
The article deals with theoretical issues of property insurance. Attention is paid to the freight insurance as one of the kinds of property insurance and the problems, arising in modern Ukraine in the process of development of the insurance business.